2015
DOI: 10.1002/jcb.25104
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Control of Hematopoietic Cell Differentiation and Leukemia

Abstract: It is now well known that in the mammalian body vitamin D is converted by successive hydroxylations to 1,25-dihydroxyvitamin D (1,25D), a steroid-like hormone with pleiotropic properties. These include important contributions to the control of cell proliferation, survival and differentiation, as well as the regulation of immune responses in disease. Here, we present recent advances in current understanding of the role of 1,25D in myelopoiesis and lymphopoiesis, and the potential of 1,25D and analogs (vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 167 publications
(191 reference statements)
0
17
0
Order By: Relevance
“…An alternative approach to improve AML therapy is to combine VDDs, including calcitriol, with other compounds. Numerous preclinical studies, principally in vitro, have shown greater differentiation potency of VDDs combined with diverse compounds, when compared to VDDs as sole agents, and were often associated with cell death [5, 6]. However, to date, most clinical trials of these combinations have not been encouraging [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to improve AML therapy is to combine VDDs, including calcitriol, with other compounds. Numerous preclinical studies, principally in vitro, have shown greater differentiation potency of VDDs combined with diverse compounds, when compared to VDDs as sole agents, and were often associated with cell death [5, 6]. However, to date, most clinical trials of these combinations have not been encouraging [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that serum VD concentration was altered in many types of diseases including cancers [8][9][10]. In leukemia, studies found that VD had potency in inducing the differentiation of leukemia cells [2,[17][18][19][20]. High serum levels of VD have been found to benefit the survival of AML patients after chemotherapy [21].…”
Section: Discussionmentioning
confidence: 99%
“…The disorder observed was the appearance of chronic myeloid leukaemia-like cells, splenomegaly, granulocytosis and thrombocytosis and reduced erythropoiesis [35]. In vitro studies have revealed that 1,25D3 and its derivatives influence the progeny of HSCs and have largely focussed on an effect on myelopoiesis [36]. We have known for many years that mouse myeloid leukaemia cells differentiate towards monocytes in response to 1,25D3 ( [37] and see below), and that 1,25D3 drives normal blood monocytes to differentiate into macrophages [38].…”
Section: The Direct Influence Of 125d3 On Stem and Progenitor Cell Dmentioning
confidence: 99%